Green, Cost-Effective Simultaneous Assay of Chloramphenicol, Methylparaben, and Propylparaben in Eye-Drops by Capillary Zone Electrophoresis - Thi Thanh Vuong Tong; Thi Thoa Cao; Nguyen Ha Tran; Thi Kim Van Le; Dinh Chi Le (Journal of Analytical Methods in Chemistry)
A green, cost-effective, and simple capillary zone electrophoresis (CZE) method was developed and validated for simultaneous determination of chloramphenicol, methylparaben, and propylparaben in eye-drops. With sodium tetraborate as background electrolyte (BGE), the apparent mobilities of chloramphenicol, methylparaben, and propylparaben increased and analysis time reduced when pH of BGE increased from 8.5 to 10.0 and concentration of BGE decreased from 40 mM to 15 mM, but complete separation of chloramphenicol from other matrix components was achieved only with sodium tetraborate concentration at 30 mM or higher and at pH = 9.3 or lower. The most suitable electrophoretic conditions for the intended application were a 30 mM sodium tetraborate solution, pH 9.3 as BGE, working voltage set at 25 kV, and UV detection at 280 nm at the cathodic extremity of the capillary. The final method was validated and proved to be reliable for assay of chloramphenicol, methylparaben, and propylparaben in eye-drops.